10 steps for hiring effective teachers - Clement, Mary C. (Thousand Oaks : Corwin A SAGE Company, 2015)
School administrators are rarely trained in hiring strategies, yet a school's faculty is pivotal for student success. Principals, assistant principals, and personnel directors all need this book as a guideline and blueprint for their hiring. Often educators rely on'gut' feelings to hire new teachers and there has to be a better way.
Includes bibliographical references and index.
Description based on XML content.
Keywords: Teachers -- Selection and appointment -- United States; Teachers -- Recruiting -- United States; First year teachers -- Training of -- United States